PENDIDIKAN GIZI SEBAGAI INTERVENSI SPESIFIK UNTUK PENINGKATAN PENGETAHUAN, TINGKAT KONSUMSI, DAN KADAR HEMOGLOBIN REMAJA PUTRI - Norma - Hapsari; Dila Ayu Puspitasari; Sugeng Iwan Setyobudi; I Dewa Nyoman Supariasa; Sutomo Rum Teguh Kaswari; Nur Rahman; Umi Fahmida (Jurnal Pendidikan Kesehatan, 2019)
In Indonesia showed that the number of anemia prevalence in adolescent girl equals to 30 percent. In Malang district, the prevalence of anemia in adolescent girl equals to 20,28 percent. In case, because of the situation, giving a trial of education about nutrition balance to reduce the case of anemia in adolescent girl in Malang district. The type of this research is an evaluation study with pre experimental design with one group pretest and posttest. The evaluation in nutrition education are used for the function to explain the phenomenon that occurs because giving a nutrtional education. This research was be held on October until December 2017. The population was take from 4 Senior High School, that is SMAN 1 Gondanglegi, SMA Islam Kepanjen, SMAN 1 Lawang, and SMAN 1 Singosari. The number of respondents in this study is 135 persons. Education intervention was given by module about balance nutrition with 20 material for 3 months. The result of this study showed that the difference between the level of knowledge before and after nutritional education were significant, showed by the average number of pretest about knowledge is 56,68, and the average number of posttest about knowledge is 66,67. The average of consumption rate increased after intervention compared before intervention, but at the average of vitamin A consumption was decreased after education but the number of consumption rate above the number of nutritional adequacy rate. The number of anemia also decreased after nutritional education. Before educations the amount of anemia respondent are 121 persons, then decreased be 93 person after education. So that, Nutritional education with variative education is required suistainable for adolescent girl, as part as prevention of nutrient anemia during pregnancy while to prevent low birth weight cases.